Developing neuro-oncology clinical trials in low- and middle-income countries: a scoping review of the current literature - Mohammad Hamza Bajwa; Faiza Urooj; Hafiza Fatima Aziz; Ahsan Ali Khan; Kaynat Siddiqui; Rabeet Tariq; Muhammad Shakir; Muhammad Ehsan Bari; Syed Ather Enam (Journal of the Pakistan Medical Association, 2024)
Low- and middle-income countries (LMICs) have historically been under-represented in clinical trials, leading to a disparity in evidence-based recommendations for the management of neurooncological conditions. To address this knowledge gap, we conducted a scoping review to assess the current literature on clinical trials in neuro-oncology from LMICs. The eligibility criteria for inclusion in this review included clinical trials registered and conducted with human subjects, with available English language text or translation, and focussed on neuro-oncological cases. The literature search strategy captured 408 articles, of which 61 met these criteria, with a significant number of randomised controlled trials from specific LMICs. The review found that LMIC clinical trials have contributed significantly to understanding surgical, chemotherapeutic, and radiation therapy interventions for brain tumours, paediatric cancers, and the repurposing of drugs as new targets in neuro-oncology. These findings highlight the potential for expanding clinical trials research in neuro-oncology in LMICs, which may significantly impact global understanding and management of these conditions, particularly from diverse populations from the global south. Keywords: neuro-oncology, brain tumour, drug Repositioning